Assessment of phosphorus associated with Fe and Al (hydr)oxides in sediments and soils - Jan, Jiří (Jihočeská univerzita, 2016)
The established fractionation scheme of Psenner and Pucsko with consecutive BD and NaOH steps was shown to be ineffective in distinguishing between the stable crystalline (hydr)oxides and their more active amorphous and poorly crystalline forms. These forms highly vary in their ability to sorb P and thus in their ecological significance. Dissolution kinetics of the Fe and Al minerals were performed using both the BD and NaOH extraction solutions. The results were applied to modify the original fractionation scheme for better quantification of P associated with active Al and Fe (hydr)oxides, and better estimation of the amounts of these Fe and Al forms in soils and sediments.
Assessment of phosphorus associated with Fe and Al (hydr)oxides in sediments and soils
Keywords: phosphorus; iron; aluminum; fractionation; sediment; soil; phosphorus; iron; aluminum; fractionation; sediment; soil